2017
DOI: 10.2147/ott.s122803
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Nrf2 signaling pathway in the radiation tolerance of patients with head and neck squamous cell carcinoma: an in vivo and in vitro study

Abstract: We aimed to investigate the relationship between the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway and the radiation tolerance of patients with head and neck squamous cell carcinoma (HNSCC). From January 2015 to January 2016, 117 patients with HNSCC were enrolled in our study and assigned into the sensitive and tolerance groups based on curative effect. Immunohistochemistry (IHC) was conducted to measure protein expressions of Nrf2, heme oxygenase-1 (HO1), NADPH quinine oxidoreductase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…It has been demonstrated that in HPV-negative HNSCC cells, activation of Nrf2 is also associated with resistance to treatment [66] and conversely, its deactivation induces radiosensitivity. This Nrf2 activation in HNSCC is also associated to the upregulation of HO-1, NQO1 and GST, which are effective antioxidants (Figure 1) [67].…”
Section: Nuclear Factor (Erythoid-derived 2)-like 2 (Nrf2) Inducesmentioning
confidence: 99%
“…It has been demonstrated that in HPV-negative HNSCC cells, activation of Nrf2 is also associated with resistance to treatment [66] and conversely, its deactivation induces radiosensitivity. This Nrf2 activation in HNSCC is also associated to the upregulation of HO-1, NQO1 and GST, which are effective antioxidants (Figure 1) [67].…”
Section: Nuclear Factor (Erythoid-derived 2)-like 2 (Nrf2) Inducesmentioning
confidence: 99%
“…Similarly, inhibition of NRF2 by siRNA in the radiation resistant HSC-4 cell line led to decreased cell viability compared to their control counterparts. Subcutaneous injection of HSC-4 cells showed that tumor size, volume and weight were significantly reduced upon radiotherapy and more obvious when NRF2 was silenced [84].…”
Section: Upr and Response To Current Hnscc Treatmentsmentioning
confidence: 99%
“…Dysregulation of the NRF2 pathway is an established mechanism of radiation resistance of human tumors and mouse models of cancer (28,29). NRF2 acts as a master transcriptional regulator of the cellular response to oxidative stress and alters the response to radiation by reducing intracellular reactive oxygen species (ROS) and DNA damage (28,30).…”
Section: Brainstem Gliomas Lacking Both P53 and Ink4a/arf Are Resistamentioning
confidence: 99%